USWAG! Comval designing a new brochure template for Compostela Valley Province (A Print Production Thesis) - Ramos, Teresita C.
Compostela Valley has an existing brochure - Conquer! Compostela Valley. This brochure features Comval as a eco-adventure tourism destination. But shown in the pictures are mining sites, which is not parallel to eco-adventure tourism. This certain problem became the inspiration of the designer in making a new brochure template that would promote not only the natural resources but all that descriptions for the attractions. She made them into reality by gathering data and using this data in making designs. With the help of some friends and some people from the provincial office, the designer became successful in making a new design template for Compostela Valley Province. The aim of this thesis is to create a new design template that would promote Compostela Valley Province as a tourist destination by presenting the different tourist attraction the province have. The different elements of design were applied in making the design templates. The designer believes that beautiful designs are important but she also thought that it is also important to communicate well with the target market using the produced material
Thesis, Undergraduate (BA Communication Arts) -- U. P. in Mindanao
Keywords: Communication Arts -- Media arts